Oxygen uptake and ventilatory threshold in swimming - Morais, P.; Cardoso, C.; Faria, V.; Rocha, S.; Machado, L.; Fernandes, R.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to identify, in terms of percent-age of maximal oxygen uptake (%VO2max), the intensity of swimming associated with a non linear increase of minute Ventilation (Ve), also described as ventilatory threshold (VT). Twenty nine trained swimmers participated in our study: 15 males and 14 females. Each subject performed a intermittent incremental protocol of 200m stages, with increases of 0.05m.S-1, and 30s intervals between each stage. VT was assessed by Ve/VO2 curve modelling method (least square method). It was assumed VT to be the intersection point, at the maximal fit Situation, of a combined pair of regressions (linear and exponential). The analysed values of VO2 and Ve were cropped by direct oximetry. The present study demonstrated that the non linear increase of Ve corresponding to VT in a specific swimming Situation seems to happen at 84.3±8.7 %VO2max